Post-truth claims and the wishing away of brute facts. (February 2020) - Spector, Bert
Post-truth claims making has, since 2016, emerged as a defining cultural and political phenomenon. It involves an assertion, made from a position of power, based on an inaccurate description of objective facts. It is a lie, to be sure, but not one intended to be taken literally. Rather, it is meant to be taken as faithful to and reflective of some deeper perceived truth. In this essay, I advance the argument that post-truth claims making is not some pernicious outgrowth of post-modernist/social constructionist theorizing, and not simply a new term for lying. Rather, it involves a particular kind of pact between claims maker and intended audience in which the leader lies by asserting inaccurate claims, expecting the intended audience to put aside that acknowledged inaccuracy in support of a belief in some shared goal. Reliance on post-truth claims helped fuel the rise of mid-20th century authoritarians, and is now a tool of authoritarian political leaders posing as populists.